Prevalence and Antimicrobial Susceptibility Profile of Staphylococcus aureus in Milk and Traditionally Processed Dairy Products in Addis Ababa, Ethiopia. (16th July 2021) - Lemma, Fikirte; Alemayehu, Haile; Stringer, Andrew; Eguale, Tadesse
Abstract : Staphylococcus aureus is a contagious pathogen that can cause various diseases in both humans and animals. Antimicrobial-resistant S. aureus is becoming an extremely important global health problem. A cross-sectional study was conducted from December 2019 to May 2020 to assess the occurrence of S. aureus and its antimicrobial susceptibility profiles in milk and traditionally processed dairy products in selected subcities of Addis Ababa. A total of 255 dairy product samples (175 raw milk and 80 traditionally processed dairy products) were collected from farms and retail markets. Samples were cultured for S. aureus according to standard microbiology techniques, and the Kirby–Bauer disk diffusion method was used to assess antimicrobial susceptibility of isolates to a panel of 12 antimicrobials. Susceptibility to methicillin was determined based on the sensitivity of isolates to cefoxitin, and resistant isolates were investigated for the presence of mec A and mec C genes using PCR. Staphylococcus aureus was isolated from 43 (24.6%) of milk, 7 (17.5%) of yogurt, and 2 (5%) of cottage cheese. A significantly higher rate of contamination with S. aureus was recorded among milk samples compared to yogurt and cottage cheese (p = 0.019 ). Out of 52 S. aureus isolates investigated for susceptibility to 12 antimicrobials, 49 (94.2%) of the isolates were resistant to ampicillin and 42 (80.8%) to amoxicillin+clavulanic acid. Twenty (38.5%) of the isolates were methicillin-resistant S. aureus (MRSA) based on susceptibility to cefoxitin. However, only one of these isolates (5%) was positive for mec A gene, and none of them were positive for the mec C gene. There was no significant difference (p > 0.05 ) in the rate of occurrence of MRSA among isolates from different sources. In conclusion, this study demonstrated a significant level of contamination of milk and dairy products with S. aureus and most isolates were multidrug resistant. The occurrence of MRSA in raw milk and dairy products signifies a serious public health threat as the practice of consuming raw dairy products in the study area is widespread. The lack of agreement between phenotypic and genotypic detection of MRSA suggests the need for further study to identify the genetic basis for the observed resistance phenotype.